State violence and genocide in Latin America: the Cold War years - Esparza, Marcia; Huttenbach, Henry R.; Feierstein, Daniel (Critical terrorism studies, 2010)
Introduction : globalizing Latin American studies of state violence and genocide / Marcia Esparza -- US hemispheric hegemony and the descent into genocidal practices in Latin America / Luis Roniger -- Political violence in Argentina and its genocidal characteristics / Daniel Feierstein -- Genocide in Chile? An assessment / Maureen S. Hiebert and Pablo Policzer -- Understanding the 1982 Guatemalan genocide / Marc Drouin -- "Industrial repression" and Operation Condor in Latin America / J. Patrice McSherry -- The United States and torture : lessons from Latin America / Jennifer K. Harbury -- State violence and repression in Rosario during the Argentine dictatorship, 1976-83 / Gabriela Aguila -- US-Colombian relations in the 1980s : political violence and the onset of Unión Patriótica genocide / Andrei Gómez-Suárez -- Political violence, justice, and reconciliation in Latin America / Ernesto Verdeja -- Vicious legacies? State violence(s) in Argentina / Guillermina S. Seri -- Courageous soldiers (valientes soldados) : politics of concealment in the aftermath of state violence in Chile / Marcia Esparza -- Bringing justice to Guatemala : the need to confront genocide and other crimes against humanity / Raúl Molina Mejía -- Conclusions : unfinished business : in search of the next agenda / Henry R. Huttenbach